Penggunaan Disfemisme Sebagai Perlambangan Kesantunan Dalam Kalangan Masyarakat Melayu Di Daerah Melaka Tengah - Rabiatul Adawiyah, Ab.Sattar (Universiti Malaysia Sarawak, (UNIMAS), 2025)
This study examines the use of dysphemism as a symbol of politeness among the Malay community in Melaka Tengah district. Dysphemism is often associated with negative and impolite connotations in communication. However, this study aims to demonstrate that in certain cultural contexts, dysphemism is not merely a crude expression but serves as a marker of familiarity, humor, and admonition. This research adopts a descriptive qualitative approach, utilizing in-depth interviews with 14 informants from Generation X and Baby Boomers who are permanent residents of Melaka Tengah district. The data is analyzed based on Allan and Burridge's Theory (1991) to categorize polite elements of dysphemism, as well as Asmah Omar’s Politeness Model (1996) to explain the symbolism of politeness in dysphemism. The findings reveal that the Malay community in Melaka Tengah employs dysphemism in daily communication to express warmth, closeness, teasing, and advice. Words such as ‘lahabau’, ‘hawau’, ‘melingkau’, ‘lahanat’ and ‘bahalul’ are not merely insults but can function as friendly expressions accepted among close speakers. The implications of this study indicate that norms of politeness are flexible, influenced by cultural and social factors within the local community. Thus, this study is expected to contribute to a deeper understanding of the function of dysphemism in Malay communication and open avenues for further research on linguistic politeness across different communities